Structures and interactions in 'bottlebrush' neurofilaments: the role of charged disordered proteins in forming hydrogel networks. (19th September 2012) - Beck, Roy; Deek, Joanna; Safinya, Cyrus R.
Abstract : NFs (neurofilaments), the major cytoskeletal constituent of myelinated axons in vertebrates, consist of three different molecular-mass subunit proteins, NF-L (low), NF-M (medium) and NF-H (high), assembled to form mature filaments with protruding intrinsically disordered C-terminal side-arms. Liquid crystal gel networks of side-arm-mediated NF assemblies play a key role in the mechanical stability of neuronal processes. Disruptions of the NF network, due to NF overaccumulation or incorrect side-arm interactions, are a hallmark of motor neuron diseases including amyotrophic lateral sclerosis. Using synchrotron small-angle X-ray scattering and various microscopy techniques, we have investigated the role of the peptide charges in the subunit side-arms on the structure and interaction of NFs. Our findings, which delineate the distinct roles of NF-M and NF-H in regulating NF interactions, shed light on possible mechanisms of disruption of optimal mechanical network properties.